Finite element simulation of reinforced concrete slabs under impact loading - Mokhatar, Shahrul Niza (2009)
In a few years ago, efforts for assessing and predicting the behaviour of concrete structures subjected to impact loads have been hampered by lack of adequate computational procedure and unavailability of good quality experimental results. Furthermore, computer software was also not yet developed up to the standards of today. Nowadays, the numerical models for the impact load assessment are starting to become more accurate and reliable. Combined with modern computer hardware, the computational time for such an assessment has been reduced to a satisfactory level. In this study, an attempt has been made to examine the accuracy of modern software with regards to assessing the response of reinforced concrete slabs subjected to impact loading near the ultimate load ranges. The response such as Time-Impact force graph, damage wave propagation, failure process of steel reinforcement, effectiveness of mesh density, effect of projectile size and final crack pattern are verified against existing experimental results. It is shown that the present general purpose finite element software is able to simulate and predict the structural behaviour satisfactorily.